Patent foramen ovale-related stroke: diagnostic approaches and the possibility of endovascular prophylaxis (clinical cases and literature review) - A. A. Kulesh; D. V. Ognerubov; S. A. Mekhryakov; E. V. Merkulov; L. I. Syromyatnikova; A. S. Tereshchenko; A. N. Samko; V. V. Shestakov; Yu. V. Karakulova (Неврология, нейропсихиатрия, психосоматика, 2020)
The paper describes three clinical cases of ischemic stroke (IS) in the presence of patent foramen ovale (PFO) in young women. The first patient has experienced two episodes of focal neurological deficit related to physical exercise. A cerebellar stroke focus was visualized by brain magnetic resonance imaging (MRI). During emotional stress, the second patient having migraine with aura developed transient weakness in the right extremities, and a stroke focus was verified in the left parietal lobe. The third patient suddenly had facial asymmetry and left arm numbness after  awakening in the morning. The patient underwent intravenous thrombolysis; control brain MRI revealed a right parietal lobe stroke. Standard examinations of all the patients established no cause of IS. Transcranial Doppler with a bubble test and subsequent transesophageal echocardiography revealed PFO that was regarded as clinically significant. Endovascular occlusion was successfully accomplished in all the patients. The paper discusses the problems of secondary prevention of PFO-related stroke and proposes an algorithm for the diagnosis and treatment of this disease.